New Designs for Phototherapeutic Transition Metal Complexes - Imberti, Cinzia; Zhang, Pingyu; Huang, Huaiyi; Sadler, Peter J. (Angewandte Chemie International Edition, 2020)
In this Minireview, we highlight recent advances in the design of transition metal complexes for photodynamic therapy (PDT) and photoactivated chemotherapy (PACT), and discuss the challenges and opportunities for the translation of such agents into clinical use. New designs for light‐activated transition metal complexes offer photoactivatable prodrugs with novel targeted mechanisms of action. Light irradiation can provide spatial and temporal control of drug activation, increasing selectivity and reducing side‐effects. The photophysical and photochemical properties of transition metal complexes can be controlled by the appropriate choice of the metal, its oxidation state, the number and types of ligands, and the coordination geometry. Light irradiation can provide spatial and temporal control of drug activation, increasing selectivity and reducing side‐effects. This Minireview summarizes new designs for light‐activated transition metal complexes which offer photoactivatable prodrugs with novel targeted mechanisms of action for use in photodynamic therapy (PDT) and photoactivated chemotherapy (PACT).